The spectrum of MEFV gene mutations and genotype-phenotype correlation in Egyptian patients with familial Mediterranean fever - Ali, Fahmy T.; Elhady, Mostafa M.; Abbas, Hanan H.; Mandouh, AbdAllah Y. (International Journal of Research in Medical Sciences, 2017)
Background: Familial Mediterranean fever (FMF) is an autosomal recessive disease mainly affecting subjects of the Mediterranean origin. It is an auto-inflammatory periodic disorder that is caused by mutations in the Mediterranean fever gene (MEFV) located on chromosome 16. Methods: The current study was designed to assess the prevalence and frequency of different MEFV gene mutations among 104 FMF clinically diagnosed Egyptian patients and to evaluate the change extent in the values of some biochemical markers (ESR, CRP, Fibrinogen-C, SAA and IL1) in different participants with different FMF severity scores. Results: According to allele status 28 patients (27%) were homozygous mutation carriers, 38 (36.5%) were with compound heterozygous mutations and 38 (36.5%) were identified as heterozygous for one of the studied mutations. Of the studied mutations, M694I, E148Q, V726A, M680I, and M694V accounted for 28.1%, 26.8%, 16.9%, and 11.3% of mutations respectively. The R761H and P369S mutations were rarely encountered mutations (1.4%). The clinical features with M694I were associated with more severe clinical course. There is a drastic elevation in the levels of estimated parameters as their levels were increased as long as the severity of the disease increased. Conclusions: The diagnosis of FMF cannot be performed on the basis of genetic testing or clinical criteria alone. So, we recommended the combination between clinical and molecular profiling for FMF diagnosis and scoring.